Development of Health Integrative Thematic Textbooks (Batik) To Provide Health Education in Elementary Schools - Sudiana, I Ketut; Adiputra, N.; Budi Adnyana, Putu (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
This research aims to develop health integrative thematic textbooks (BATIK). The method used is the Research and Development model of Borg & Gall. Based on the research, it obtained that integrated health education material in accordance with the PHBS indicator of school. Integration using two patterns, explicitly through the subtitle